(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
Nigeria’s Federal Capital Territory (FCT) of Abuja has witnessed rapid urbanization, and this urbanization has significantly impacted the development of neighbouring states with the attendant increase in air pollution. This study presents a comprehensive multi-sensor satellite assessment of the spatiotemporal fluctuations of key pollutants—nitrogen oxides (NOx), sulfur dioxides (SO₂), carbon (II) oxides (CO), methane (CH₄), ozone (O₃), and formaldehyde (HCHO), and the absorbing aerosol index (AI)—across Abuja and its neighbouring states (Nasarawa, Kogi, Niger, and Kaduna) from 2019 to 2024. Using satellite remote sensing data from Sentinel-5P/TROPOMI together with other atmospheric data, the temporal dynamics of pollutants and their connections to parameters such as ambient temperature, Normalized Difference Vegetation Index (NDVI), and precipitation have been investigated. NO2 and HCHO were found to be increasing around Suleja, Abuja, and Lokoja, as SO2 and CO were found to be decreasing, indicating an improved efficient use of fuel and emission control. A positive correlation (r = 0.62) between precipitation and ozone was found, showing there is more convective transport and photochemical production during the rainy season. The effects of plants on the absorption of air pollution were shown through the negative correlations between NDVI, CO, and AI. Methane, on the other hand, moved from north to south in space, which was the same direction as changes in the intensity of farming. The findings show how unified policies, such as proper city planning, vegetation protection, and emission reduction, are important in sprawling urban areas for air pollution reduction.